Bound for Success: A Systematic Review of Constraint-Induced Movement Therapy in Children With Cerebral Palsy Supports Improved Arm and Hand Use - Huang, Hsiang-han; Fetters, Linda; Hale, Jennifer; McBride, Ashley (Physical therapy, 2009)
Constraint-induced movement therapy (CIMT) is a potentially effective intervention for children with hemiplegic cerebral palsy (CP). The objectives of this systematic review are: (1) to investigate whether CIMT is supported with valid research of its effectiveness and (2) to identify key characteristics of the child and intervention protocol associated with the effects of CIMT. A search of MEDLINE (1966 through March 2009), Entrez PubMed (1966 through March 2009), EMBASE (1980 through March 2009), CINAHL (1982 through March 2009), PsychINFO (1887 through March 2009), and Web of Science (1900 through March 2009) produced 23 relevant studies. The 2 objectives of the review were addressed by: (1) scoring the validity and level of evidence for each study and calculating evidence-based statistics, if possible, and (2) recording and summarizing the inclusion and exclusion criteria, type and duration of constraint, intervention and study durations, and outcomes based on the International Classification of Functioning, Disability and Health (ICF). Only studies published in journals and in English were included in the systematic review. Studies varied widely in type and rigor of design; subject, constraint, and intervention characteristics; and ICF level for outcome measures. One outcome measure at the body functions and structure level and 4 outcome measures at the activity level had large and significant treatment effects (d > or = .80), and these findings were from the most rigorous studies. Evidence from more-rigorous studies demonstrated an increased frequency of use of the upper extremity following CIMT for children with hemiplegic CP. The critical threshold for intensity that constitutes an adequate dose cannot be determined from the available research. Further research should include a priori power calculations, more-rigorous designs and comparisons of different components of CIMT in relation to specific children, and measures of potential impacts on the developing brain.